The expression of BCL-G in leukemia and gastrointestinal tissues (Bangladesh Journal of Medical Science, 2017)
Background & Objective:- BCL-G is a novel protein of Bax (BCL-G associated protein X) that induces caspase-mediated apoptosis. These proteins play important roles in regulating apoptosis in both normal or neoplastic cells, however their cellular and tissue distribution remains to be determined. Thus, the current study objective was to elucidate the distribution and expression pattern of BCL-G in normal and malignant gastrointestinal human tissues.Methods:- The distribution and expression of BCL-G was measured by immunohistochemistry using a rabbit monoclonal antibody against BCL-G in formalin-fixed, paraffin embedded, benign or malignant human tissue.Results:- A variable pattern of positive expression of BCL-G was observed within all the tissues studied. BCL-G expression was found to be localized to the cytoplasmic paranuclear granules of the epithelialium in the majority of organs examined. Intensity of BCL-G staining was associated withthe maturation state of benign tissue.Conclusion:- Here we demonstrate that BCL-G exhibits a specific tissue distribution pattern that appears to correlate with cellular differentiation. While such distribution patterns are complex they provide an intriguing insight into overall function that would require further investigation to fully elucidate their physiological/pathological significance.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.433-438